TAX FAIRNESS, PERCEIVED CORRUPTION AND TAX ADMINISTRATION IN NIGERIA - Mubaraq Sanni; Benuh Adama IDRIS (Malete Journal of Accounting and Finance, 2023)
Globally, perceived unfairness and corruption in tax administration cause taxpayers to be apathetic about their tax obligations, leading to tax evasion. It is against this background that this study investigated the extent to which tax fairness moderated by perceived corruption influence tax administration in Nigeria. The study employed survey method to collect and analyse quantitative data from randomly and purposefully sampled 3,800 FIRS management staff and registered corporate taxpayers at the FIRS zonal offices. Quantitative data were analysed using partial least square – structural equation modelling (PLS-SEM). The findings revealed that there was positive and significant relationship between tax fairness and tax administration in Nigeria (β = 0.096, 2.284, p < 0.05) and positive moderating influence of perceived corruption on the relationship between Tax Fairness and Tax Administration in Nigeria (β = -0.061, t = 2.284, p < 0.05). The study therefore concluded that tax fairness and perceived corruption are good predictors of tax administration in Nigeria. The study recommended that equity, justice and fairness should be exhibited in tax administration and government should further take its fight against corrupt practices vis-à-vis taxpayers and tax revenue generating agencies in Nigeria.